¿Qué nos pueden decir los mapas de pobreza para la programación de la asistencia en alimentos? - Benson, Todd (International Food Policy Research Institute, 2003)
Poverty maps are easily used, easily understood, and objectively verifiable. Using them for politically sensitive decisions, such as where to locate food assistance projects, is likely more acceptable than basing such decisions on obscure and complex or subjective criteria. Coupled with timely information on the occurrence of events that increase the risk of households facing food shortages, poverty maps can be used to map vulnerability to food insecurity.